Od biernego odbiorcy do aktywnego mediakreatora – małe dzieci i TIK w świetle badań własnych - IWANICKA, AGNIESZKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Agnieszka Iwanicka, Od biernego odbiorcy do aktywnego mediakreatora – małe dzieci i TIK w świetle badań własnych [From passive recipients to active mediacreators: small children and ICT in the light of own studies]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 143-160. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.08 Small children show a lot of media activity: they are perfectly capable of handling new technologies, they have been using them since the first years of their life. What activities they show depends on the family home and the behaviors they observe with their parents. With their support and providing positive patterns, the child can become not only a passive media user, but also an active media content creator, a kind of mediacreator, which over time will have a real impact on the reality in which he grows up. In the article, I present some of the results of the my research, in which I checked what role the media plays in the life of a child in an early school age. I try to answer the question, what media activities are displayed by children – whether it is only passive and imitative, or maybe they are actively creating media content.